Biological evaluation of materials : the interaction of materials with their environment /: the interaction of materials with their environment. ([2022]) - Walkowiak, Bogdan, 1953-; Walkowiak-Przyby±o, Magdalena; (Ph. D. in materials science), Komorowski, Piotr
No abstract available